Processing of ceramics : breakthroughs in optical materials - Ikesue, Akio, 1958- (John Wiley & Sons, Inc., 2021)
"In the 1950's, Dr. R. L. Coble of MIT demonstrated that polycrystalline alumina ceramics can transmit light by using high purity raw materials and controlling the microstructure of ceramics. This technology has been applied to sodium discharge lamps, and today this technology is still widely used for lighting. However, the applications of ceramics to date was extremely limited due to insufficient optical quality. Nowadays optical ceramic offer a much wider range of uses such as in lenses, transmission flats, mirrors, and prisms--and active optics--for example laser gain media, frequency converters, polarizers, and adaptive optics. Manufacturing next generation optics have been and will continue to be enablers for enhancing the performance of advance laser, imaging, and spectroscopy systems"--